2020
DOI: 10.1186/s12955-020-01455-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of the musculoskeletal health questionnaire (MSK-HQ): a between country comparison

Abstract: Background: The Musculoskeletal Health Questionnaire (MSK-HQ) has been developed to measure musculoskeletal health status across musculoskeletal conditions and settings. However, the MSK-HQ needs to be further evaluated across settings and different languages. Objective: The objective of the study was to evaluate and compare measurement properties of the MSK-HQ across Danish (DK) and English (UK) cohorts of patients from primary care physiotherapy services with musculoskeletal pain. Methods: MSK-HQ was transla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
4
9
1
Order By: Relevance
“…In this study, the total score showed no floor and ceiling effects, which is consistent with former studies assessing the MSK-HQ [ 5 , 7 , 9 ]. Although, when assessing floor and ceiling effects at single items in this population, item 3 (gait) and item 4 (washing/dressing) demonstrated floor effects and item 9 (sleep) showed a ceiling effect.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the total score showed no floor and ceiling effects, which is consistent with former studies assessing the MSK-HQ [ 5 , 7 , 9 ]. Although, when assessing floor and ceiling effects at single items in this population, item 3 (gait) and item 4 (washing/dressing) demonstrated floor effects and item 9 (sleep) showed a ceiling effect.…”
Section: Discussionsupporting
confidence: 92%
“…The Norwegian population with different MSK disorders achieved a mean total score of 27.7, while the British populations scored a mean total score of 28.6 [ 5 ] and 26.6 [ 7 ]. The Danish population with MSK disorders, similar to our study, reached a higher mean score in both MSK-HQ (32.3) and EQ-5D-5L (0.69) [ 9 ]. One difference that might explain some of the differences is that only 7% of the Danish population was on sick leave and were possibly less affected of their MSK disorders [ 9 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations